O lixo eletrônico como possibilidade para o ensino de química na formação de professores - Friedrich, Leandro da Silva (2014)
Electronic waste is one of the biggest problems of the XXI century, for the increase in amount in which it is being generated, as for its varied chemical composition and toxicity of some substances present in it. However, despite showing up as such relevant theme to be discussed in classroom, it has been receiving little emphasis in the Chemistry teaching. Thus, the present paper has as its focus the discussion around the theme in the initial and continued formation of Chemistry teachers, aiming at investigating in which forms it may be approached and how it may collaborate in the formation of such teachers. For that, this research has been divided in three phases: the development of an extension activity related to the electronic waste theme (phase E1), the insertion achievement of this theme in the initial formation of Chemistry teachers (phase E2), and the elaboration and execution of a continued formation course approaching the electronic waste theme (phase E3). In the first phase, a distribution of reagent kits which allow the experimental activity achievement was carried out, being the qualitative identification of metals present in the electronic waste one of them. The participating teachers in this phase answered a questionnaire which aimed at investigating questions related to electronic waste and the participation in continued formation courses. In phase E2, two interventions with students of BSc in Chemistry of UFSM were carried out: an experimental activity of investigative character and the elaboration of class plans approaching the electronic waste theme. In phase E3 a continued formation course was developed with ten Chemistry teachers, in which activities related to electronic waste with Chemistry teaching through the contact with such residue, the discussion of texts, the class plan elaboration and analysis, as well as through the discussion about the experimental activity importance and the different teaching resources (teaching videos and books). Phase E3 also counted on the elaboration of a website which aimed at, among other actions, collecting material (articles, websites, and videos) about the electronic waste theme. Therefore, through the obtained results in all phases of this research, it was verified that electronic waste emerges as a Chemistry teaching possibility, being able to be approached in different manners. Besides that, according to the assessment of the participating teachers, the developed activities around the theme contributed with their professional formation, making possible the discussion of new ideas and strategies for their role in classroom.